2017
DOI: 10.1002/joc.5186
|View full text |Cite
|
Sign up to set email alerts
|

The first 300‐year streamflow reconstruction of a high‐elevation river in Chile using tree rings

Abstract: ABSTRACT:In central Chile, increasing demand for water and decreasing runoff volumes due to drier conditions have placed catchments in this zone under water stress. However, scarcity of observed data records increases the difficulty of planning future water supply. Instrumental records suggest a reduction in streamflow over the last 56 years. However, this change is not statistically significant and the lack of meteorological stations with long records in this mountainous region hampers a deeper analysis, moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
1
9
1
1
Order By: Relevance
“…This reconstruction offers a new long-term perspective for the entire Mediterranean region in Chile. A relevant feature of our reconstruction is the retained variance, having the highest explained variance of any streamflow reconstruction in South America (56% of total variance), and contrasting previous river reconstructions carried out in several South American rivers by authors as: Mundo et al [45], Lara et al [46,47], Urrutia et al [48], Ferrero et al [49], Muñoz et al [37], Barria et al [13,50], and Fernandez et al [51]. In statistical terms, the RE of the reconstruction was 0.53 considered good and a little higher than the other streamflow reconstructions in South America.…”
Section: The 700 Years Of Petorca River Streamflow Reconstruction Andcontrasting
confidence: 51%
“…This reconstruction offers a new long-term perspective for the entire Mediterranean region in Chile. A relevant feature of our reconstruction is the retained variance, having the highest explained variance of any streamflow reconstruction in South America (56% of total variance), and contrasting previous river reconstructions carried out in several South American rivers by authors as: Mundo et al [45], Lara et al [46,47], Urrutia et al [48], Ferrero et al [49], Muñoz et al [37], Barria et al [13,50], and Fernandez et al [51]. In statistical terms, the RE of the reconstruction was 0.53 considered good and a little higher than the other streamflow reconstructions in South America.…”
Section: The 700 Years Of Petorca River Streamflow Reconstruction Andcontrasting
confidence: 51%
“…In fact, Quintana and Aceituno (2011) in a study analyzing the changes in rainfall in central and south-central Chile found that ENSO and AAO are not independent modes of variability but rather they both affect precipitation regimes. It is also important to consider possible different seasonal effects of these modes of variability, for example those found by Barria et al (2017), who, utilizing a 11-year moving average of a 300-year tree-ring streamflow reconstruction for the upper Biobío river, determined a negative correlation between the Pacific Decadal Oscillation (PDO) and streamflow during the snowmelt season (October-March) while a positive correlation between the SAM and that seasonal streamflow. Thus, we believe that the SAM-streamflow statistical relationship we found should be tested further in order to develop more accurate predictive models of extreme interannual dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the ENSO influence on drought events is also documented for much longer time scales (i.e. centuries) by analysing tree rings (Barria, Peel, Walsh, & Muñoz, ) or archaeological remains (Gayo, Latorre, Santoro, Maldonado, & de Pol‐Holz, ). Overall, the influence of ENSO on drought indices and their spatio‐temporal dynamics were assessed for several regions in Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the ENSO influence on drought events is also documented for much longer time scales (i.e. centuries) by analysing tree rings (Barria, Peel, Walsh, & Muñoz, 2018) or archaeological remains (Gayo, Latorre, Santoro, Maldonado, & de Pol-Holz, 2012 2 | DATA AND METHODS…”
Section: Introductionmentioning
confidence: 99%